Conflict management in friendship relationships based on gender among social science education students - Rezi Sara; Sri Buwono; Yusawinur Barella; Maria Ulfah; Venny Karolina (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine whether there is a difference in the way males and females encounter conflict to find a resolution in friendship relationships among Social Studies Education students. The research employs a quantitative approach with a survey method using purposive sampling, involving a total of 91 participants who have experienced conflicts, consisting of 26 male students and 65 female students. Data collection utilizes a questionnaire adapted from Johnson, and data analysis employs descriptive statistics. The results indicate that 1) conflict management strategies employed by male and female students in friendship relationships within Social Studies Education predominantly involve collaboration, with an average percentage score of 21.38 for male students and 21.45 for female students, and 2) the research findings based on gender differences show (p > 0.05 = 0.67 > 0.05, t = 0.42, df = 89), indicating no significant difference in conflict management between male and female students.